La Evaluación En El Proceso De Enseñanza- Aprendizaje En La Asignatura De Inglés - Rodríguez Arellano Nancy Georgina; Enrique Jesús Guambo Yerovi (European Scientific Journal, ESJ, 2018)
The objective of the present research is to determine the incidence of the evaluation in the academic performance of the students of the ninth years of Basic Education in the subject of English. For this, the strengths and weaknesses of the evaluation were identified as part of the pedagogical, didactic strategies applied, the teacher's performance in the classroom, the interpersonal relationships and the treatment or approach that the teachers of the specialty demonstrate with the students. The research was based on the critical-propositive paradigm. A review of the literature on pedagogical models and its impact on the evaluation of learning was made, to then establish the level of relationship between teacher and student in the teaching-learning process. The modality, type and level were identified with a global vision of cognitive totality and/or of skills, objectives, hypotheses and operationalization of variables. Through a questionnaire, the information was collected and a logical, mathematical and statistical model was established in order to demonstrate the impact of evaluation on learning, taking as a reference the desired and expected frequencies. It was established that Teachers by means of active techniques developed and impacted through the evaluation on meaningful knowledge.